Modes of use and preservation of digital information resources as a support to the learning process at the Faculty of humanities and social sciences in Zagreb - Vrana, Radovan (Array, 2013)
The aim of this paper is to present results of the research among students at the Faculty of humanities and social sciences in Zagreb (FHSS) on two important topics: students' use of digital information resources and preservation of these digital information resources. To find out more about these two topics, a research study was designed. The results confirmed that digital information resources are very popular among students for use in their education. The results also indicated the need of students to have constant access to digital information resources and to be able to store a selection of resources on their computers. The results also showed that students want digital information resources used in education to be available indefinitely and that their teachers should be responsible for care for digital information resources used in education, which is rather peculiar. Students think that digital information resources still cannot replace printed information resources. The results indicate lack of information about students’ needs and attitudes about access and use of digital information resources in education for the purpose of development of university policies on organization and preservation of digital information resources for use in higher education.